Role of Pregabalin in Reducing Postoperative Analgesic Requirement of Patients Undergoing Knee Arthroscopy Anterior Cruciate Ligament Repair - Waseem Younis, Shahid Rasool Dar, Noman Tariq, Faheem Asghar, Shumaila Ashfaq, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To assess the effect of pregabalin in reducing the postoperative requirement of analgesics of patient undergoing knee arthroscopic anterior cruciate ligament repair surgery. Study Design: Prospective randomized control trial. Place and Duration of Study: Department of Anesthesia, Ghurki Trust Teaching Hospital Lahore from 1st June 2021 to 31st December 2021. Methodology: Eighty patients were randomly divided into two groups; group A and group B, each group comprised 40. Group A receive placebo and group B receive pregabalin 150mg once a day for two days after surgery. Pain assessment done with the help of Numeric Rating Scale and rescue analgesia was recorded. Results: The mean age was 31±10.2 years of group A and 33±10.3 year of Group B. There were more males within both groups in comparison to females with a percentage of 77.5% and 85% respectively. The reduction was seen within Group B in comparison of Group A in terms of ASA class, VNRS, and maximum sensory block. Cumulative volume of PCA in ml was also less in group B than group A with a significant difference within 0-6 hours. Conclusions: The use of pregabalin 150mg after surgery for two days significantly reduces the analgesic consumption Keywords: Pregabalin, Postoperative analgesic, Numeric rating scale